Coronavirus disease (covid-19) and public health issues in developing countries-focus on biomedical waste management - Kuljeet Singh Anand; Bhuwan Sharma; Rakesh Kumar Mahajan; Sanjeet Panesar; Prachi Dubey (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
India as a 2nd largest populous country with a high population density with lack of awareness, burden of neglected tropical diseases and a rising prevalence of non communicable diseases, have overburdened health infrastructure. In such conditions Covid-19 pandemic is stretching the health system to its limit. Most of population is a daily wager; unawareness is there already for many basic habits. There is poor access to safe food availability, safe water and sanitation, poor food storage facility or access to processed foods , affordability of processed foods and necessity supply chain are lacking. All such aspects have a public health importance. Meanwhile to protect the community from the covid infection has led to an increase in the Biomedical Waste (BMW) production for which no separate guideline is formulated as the WHO guidelines for waste management suffice to manage covid related waste too. The segregation of COVID waste as per requirements of Schedule I of the BMW Management Rules 2016 with some additional safety criteria is sufficient to handle the waste. The waste generated at hospital and quarantine camps or houses if handled according to the guidelines then the problem can be steadily tackled with minimum problems.This pandemic Covid-19 disease can be used as a tool to educate the population. "Empowering masses about modes of transmission, debunking myths, associated risks and preventive strategies" and this will be is a cost effective key instrument not only for Covid 19 but also for other infectious disease.